Drivers of Employee Performance in A Municipal Market Enterprise: The Roles of Job Satisfaction, Work Ethic, And Work Environment - I Komang Oka Permadi; I Gusti Ngurah Agung Gede Eka Teja Kusuma; Anak Agung Ngurah Wisnu Pramana Ningrat (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
This study examines the effects of job satisfaction, work ethic, and the work environment on employee performance at the Badung Market Unit of Perumda Pasar Sewakadarma, Denpasar, Indonesia. As a municipal enterprise, the organization depends on effective human resource management to maintain service quality and achieve operational objectives. A quantitative research design was employed, involving all 60 employees through a saturated sampling or census technique. Data were collected using questionnaires, interviews, and documentation. The questionnaire served as an instrument for measuring the research variables, while the data were analyzed using multiple linear regression with SPSS version 25.0. The findings demonstrate that job satisfaction has a positive and significant effect on employee performance, indicating that employees who are more satisfied with their jobs tend to perform better. Work ethic also has a positive and significant influence, suggesting that discipline, responsibility, commitment, and dedication contribute to improved work outcomes. In addition, a supportive work environment significantly enhances employee performance by promoting comfort, cooperation, and effectiveness in task completion. These results confirm that employee performance can be strengthened by improving job satisfaction, reinforcing a strong work ethic, and creating a conducive work environment. The findings provide implications for policies aimed at enhancing performance.